Strength of association between umbilical cord pH and perinatal and long term outcomes: systematic review and meta-analysis - Malin, Gemma L (BMJ Publishing Group Ltd., 2010)
Objective To evaluate the association between umbilical cord pH at birth and long term outcomes. Design Systematic review and meta-analysis. Data sources Medline (1966-August 2008), Embase (1980-August 2008), the Cochrane Library (2008 issue 8), and Medion, without language restrictions; reference lists of selected articles; and contact with authors. Study selection Studies in which cord pH at birth was compared with any neonatal or long term outcome. Cohort and case-control designs were included. Results 51 articles totalling 481 753 infants met the selection criteria. Studies varied in design, quality, outcome definition, and results. Meta-analysis carried out within predefined groups showed that low arterial cord pH was significantly associated with neonatal mortality (odds ratio 16.9, 95% confidence interval 9.7 to 29.5, I(2)=0%), hypoxic ischaemic encephalopathy (13.8, 6.6 to 28.9, I(2)=0%), intraventricular haemorrhage or periventricular leucomalacia (2.9, 2.1 to 4.1, I(2)=0%), and cerebral palsy (2.3, 1.3 to 4.2, I(2)=0%). Conclusions Low arterial cord pH showed strong, consistent, and temporal associations with clinically important neonatal outcomes that are biologically plausible. These data can be used to inform clinical management and justify the use of arterial cord pH as an important outcome measure alongside neonatal morbidity and mortality in obstetric trials.